1989
DOI: 10.1346/ccmn.1989.0370302
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Faults in the Kaolin-Group Minerals: Defect Structures of Kaolinite

Abstract: Abstract-Previous studies of the defect structure of kaolinite have examined samples having a restricted level of defects. This study examined nine kaolinite samples having a large diversity of defect contents, as indicated by Hincldey indexes ranging from 1.44 to 0.18. The samples were chosen so as to cover this range in as regular a manner as possible. The types and abundances of the defects were determined by examining the X-ray powder diffraction profiles for the 02,11 and 20,13 bands. The diffraction inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(46 citation statements)
references
References 19 publications
3
41
0
2
Order By: Relevance
“…Os resultados dos índices R e a estimativa do padrão interno obtidos foram insatisfatórios (dados não apresentados). Dessa forma, e baseando-se na descrição da possibilidade de presença conjunta de caulinita triclínica e caulinita com caráter monoclínico (Plançon & Tchoubar, 1977;Brindley et al, 1986;Plançon et al, 1989) (Brasil, 1971).…”
Section: Resultados E Discussão Caracterização Mineralógica Dos Solosunclassified
See 1 more Smart Citation
“…Os resultados dos índices R e a estimativa do padrão interno obtidos foram insatisfatórios (dados não apresentados). Dessa forma, e baseando-se na descrição da possibilidade de presença conjunta de caulinita triclínica e caulinita com caráter monoclínico (Plançon & Tchoubar, 1977;Brindley et al, 1986;Plançon et al, 1989) (Brasil, 1971).…”
Section: Resultados E Discussão Caracterização Mineralógica Dos Solosunclassified
“…Plançon & Tchoubar (1977) e Plançon et al (1989) relataram que esses aspectos são comuns em caulinitas com alta desordem estrutural e, conforme classificação proposta por esses autores, enquadram-se no grupo 3, o qual classifica as caulinitas com caráter monoclínico. A R. Bras.…”
Section: Grau De Desordem Estrutural Da Fração Menor Que 02 μMunclassified
“…Although Young and coworkers concluded that the non-H portion of the structure largely obeys C-centering, the important result of the P1 refinements was that OH groups that are equivalent in C1 exhibited two different orientations in P1. These orientations have important effects, for example, in vibrational spectroscopy (e.g., Brindley et aL, 1986;Johnston et al, 1990), the calculation of X-ray powder diffraction patterns (e.g., Bookin et aL, 1989;Plancon et aL, 1989), and electrostatic modeling of the structure (e.g., Abbott, 1989;Guthrie and Bish, 1991). Thus, it is crucial to examine the available evidence concerning the true space group.…”
Section: The Space Group Of Kaolinitementioning
confidence: 99%
“…Particle shape of kaolinite is regular and pseudohexagonal. One of substantial parameters affecting the utilization of kaolins is the "crystallinity" or degree of structural ordering of kaolinite (Plançon & Tchoubar 1977a,b;Plançon et al 1988Plançon et al , 1989Bookin et al 1989). The level of kaolinite ordering is usually expressed by indices calculated from their X-ray diffraction patterns (Hinckley 1963;Plançon & Zacharie 1990;Aparicio et al 2006).…”
Section: Introductionmentioning
confidence: 99%